The illiberal model of state capitalism in Poland - Piątek, Dawid (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: There is growing awareness that a new model of capitalism is emerging. The 2008–2009 Global Financial Crisis was a catalyst for redefining the role of the state in the economy, and as a result state involvement in the economy has been on the rise since then. We can also observe changes in political situation: democracy has been backsliding globally, authoritarian, and populist tendencies are growing. In some countries, those two tendencies are present, and as a result the illiberal model of state capitalism emerged. In recent years, in Poland, state involvement in the economy was growing and authoritarian tendencies were visible. In this context, it is worth asking if there is an illiberal model of state capitalism in Poland? Aim: The aim of the presented paper is to evaluate the political and economic situation in Poland and to check whether there are changes that could be interpreted as building illiberal state capitalism. Results: The results indicate that in Poland many illiberal statist tendencies could be identified.